Effect of Marketing Mix towards the Usage of ATMs (Automatic Teller Machines) - Faritzal, Adam; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The growth of the banking market in Indonesia, especially after the era of banking deregulation, is a growth in the retail banking market segment. The growth of the retail market segment is of course an opportunity for banking business players to be able to effectively cover it in need of strategies and relevant tips to anticipate it. The market has unique properties. The market is always changing and dynamic, especially in the modern world as it is today. Faced with this reality, companies are required to be able to develop marketing policies that are active and always keep abreast of technological and economic developments. An active and more market-oriented marketing policy brings the banking business to the absolute necessity of defining the needs and desires of consumers, not from the company's point of view. Thus, the company can understand what the real needs and desires of consumers are.